Peningkatan Pemahaman Materi Laju Reaksi Melalui Model Pembelajaran Project Based Learning Siswa Kelas Xi SMAN 1 Teluk Bintan - Mustamid; Dody Irawan (Yayasan Azhar Amanaa Yogyakarta, 2026)
This study aims to analyze the improvement of students’ understanding of reaction rate material through the implementation of the Project Based Learning model among eleventh-grade students at SMAN 1 Teluk Bintan. This research used a quantitative approach with a quasi-experimental method and a pretest-posttest control group design. The research sample consisted of two classes, namely an experimental class with 32 students and a control class with 31 students. The experimental class received instruction using the Project Based Learning model, while the control class received conventional instruction. Data were collected through a conceptual understanding test, student activity observation, and documentation. The results showed that the average pretest score of the experimental class was 56.81 and increased to 84.37 in the posttest. The control class obtained an average pretest score of 55.67 and increased to 73.45 in the posttest. The t-test result showed a significance value of 0.000 < 0.05, indicating a significant effect of Project Based Learning on students’ conceptual understanding. The N-Gain score of the experimental class was 0.68, which was categorized as moderate, while the control class obtained an N-Gain score of 0.39, which was categorized as low. Therefore, Project Based Learning is effective in improving students’ understanding of reaction rate material.